2003
DOI: 10.1023/a:1022088005887
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The prevalence and serotypic diversity of Mannheimia [Pasteurella] haemolytica and Pasteurella trehalosi from nasal swabs, sera and abattoir specimens from sheep in the highlands of Wollo, North East Ethiopia was investigated. Prevalence rates of 83% and 75% of these microorganisms were found in the serum samples and nasal swabs, respectively, from apparently healthy sheep. In a local abattoir, 205 lungs were investigated, 34% of which showed pneumonia, from which samples were collected from 51 lungs and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The overall seroprevalence of ovine pasteurellosis in this study was 90.17% which is comparable to the 100 and 83% seroprevalence reported by Berhe et al ( 11 ), and Sisay and Zerihun ( 8 ). This high prevalence is an indirect indication that the disease is negatively impacting sheep productivity as well as the livelihood of smallholder farmers which calls for urgent and effective interventions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The overall seroprevalence of ovine pasteurellosis in this study was 90.17% which is comparable to the 100 and 83% seroprevalence reported by Berhe et al ( 11 ), and Sisay and Zerihun ( 8 ). This high prevalence is an indirect indication that the disease is negatively impacting sheep productivity as well as the livelihood of smallholder farmers which calls for urgent and effective interventions.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, we reported six (6) serotypes at different levels of occurrence as followed: A1 (39.17%), A2 (74.83%), A7 (77.83%), P. multocida serotype A (60%), T4 (62%), and T15 (64%). Higher or lower seroprevalence of distinct serotypes could be reported at varied frequencies in different areas ( 8 , 11 , 12 , 17 , 41 – 43 ) due to variation in sample size, laboratory methods used, management practices, level of environmental stressors, or exacerbating factors, climatic factors, and occurrence of concurrent pathogens ( 9 ). Different serotypes can be associated with a wide range of clinical diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. haemolytica and B. trehalosi belong to different distinct clusters in phylogenetic analysis using the rpo B gene, a gene encoding for the β subunit of bacterial RNA polymerase [37]. The association of M. haemolytica with significant proportion of ovine pneumonic cases in the current study is in line with those mentioned by Sisay and Zerihun [26], Ayelet et al [5], and Deressa et al [22] in central highlands and Eastern Ethiopia where all indicated M. haemolytica as the main culprit of the problem. Thus, the current finding along with previous reports of the high prevalence of M. haemolytica serotype A2 and A8 in other parts of central Ethiopia [5] all consolidate the need for polyvalent vaccine unlike the currently used monovalent vaccine (inactivated P. multocida biotype A).…”
Section: Discussionsupporting
confidence: 85%
“…In Ethiopia, a monovalent vaccine (inactivated P. multocida biotype A) produced at the National Veterinary Institute (Ethiopia) is being used for vaccination against ovine pasteurellosis although studies in central highlands of Ethiopia indicate M. haemolytica serotype A2 and A7 were reported to occur at high frequency [5, 26]. Although there is no published report on the efficacy of the currently used vaccine under field conditions, customer complaints on the high rates of mortality and morbidity following respiratory distress in different parts of the country have been documented despite the annual vaccination.…”
Section: Introductionmentioning
confidence: 99%